Biological Functions of Tea Polyphenols Based on Their Active Substances - He, Junyi (Transactions on Environment, Energy and Earth Sciences, 2024)
Tea polyphenols are a type of polyphenolic compounds with a phenolic hydroxyl structure, commonly found in tea trees and with higher concentrations in green tea. They are recognized as key functional elements of tea and exhibit various biological functions, such as antioxidant, metabolic regulation, and antibacterial properties. These characteristics have aroused great interest in different industries, including functional foods, drug research, and food preservation methods. In recent years, research has been conducted on the extraction process of tea polyphenols, exploring their characteristics, biological effects, flavor regulation, mechanism of action, and potential applications. This detailed study provides valuable reference for the development of functional foods, natural therapies, and other related products containing tea polyphenols. The multiple advantages and uses of tea polyphenols highlight their potential to enhance health and well-being in a range of industries. The ongoing research on tea polyphenols emphasizes their importance as natural compounds with encouraging biological effects and functional qualities, which can be used to develop various health enhancing products and applications.